Al-Qur’an Digital (Ragam, Permasalahan dan Masa Depan) - Syarif Hidayat (Kopertais Wilayah III Yogyakarta, 2018)
Digital Qur’an actually emerged from the spirit of the age that continues to go forward and go forward toward the changes that further facilitate human affairs. The development of more advanced age are encouraged with the progress of technology in all areas of course will give you an idea that the Koran digital future will also continue to grow, both in terms of variety, quality and quantity. Progress of the Koran digital future will certainly be very closely associated with the development of information and communication technology. If the present development of computer technology leads to ease of use in life, especially closer to the direction of the functions possessed by the senses, good eyesight, hearing, touch, taste and smell. Mature hardware technology brings many changes, especially technological data input. The technology is often used to facilitate data input in the form of text is the use of OCR technology (Optical Character Recognition), OCR technology is the process of translating the character (image character) into text form by matching the pattern of characters per line with a pattern that has been stored in a database application, The results of the OCR process is the appropriate form of text that appears in the output image scanner in which the accuracy of the translation of a character depends on the level of image clarity. This fact also deserve special attention in view of the data input is critical data for all Muslims.